(untitled) (The International Journal for Scientific Research, 2026)
Scientific research is undergoing rapid transformation with the expanding use of artificial intelligence applications, which have introduced fundamental changes across different stages of the research process. This study aims to examine the reality of artificial intelligence use in scientific research among researchers in Sudanese universities, analyze their level of awareness of these applications, and identify the main technical and ethical challenges associated with their use. The study adopts a descriptive analytical approach, and data were collected through an electronic questionnaire administered to a random sample of 320 university faculty members, which was generated from a real 60-member random sample. Data were analyzed using appropriate descriptive statistical techniques. The findings indicate a high level of awareness of artificial intelligence applications, accompanied by noticeable variation in actual usage levels, with usage concentrated in specific applications such as literature search tools and chat-based reports. The results also show that technical challenges related to digital infrastructure, along with ethical concerns related to privacy and academic integrity, have a statistically significant effect on the level of artificial intelligence utilization. Clear institutional policies and ethical frameworks are essential for responsible adoption.